Optimisation of particle filters using simultaneous perturbation stochastic approximation - Chan, T; Doucet, A; Tadic, V; IEEE; IEEE; IEEE (2003)
This paper addresses the optimisation of particle filtering methods aka Sequential Monte Carlo (SMC) methods using stochastic approximation. First, the SMC algorithm is parameterised smoothly by a parameter. Second, optimisation of an average cost function is performed using Simultaneous Perturbation Stochastic Approximation (SPSA). Simulations demonstrate the efficiency of our algorithm.